Experience and struggle of a survivor of eye mutilation by rubber bullets - Guillot, Carles (Torture Journal, 2024)
My name is Carles Guillot and I am 52 years old. On 17 July 2001, 23 years ago now, during a protest against the illegal assault and eviction of a squatted house, the Kasa de la Muntanya, a national police officer shot me point-blank in the face and permanently damaged my right eyeball. As the neighbourhood was taken over by the police, we had to wait a few hours before we could go to a hospital. Finally, some colleagues took me to the Bellvitge Hospital, the furthest hospital in the area, to avoid being identified by the police. The prognosis was clear: I would be one-eyed for life.